2011
DOI: 10.1016/j.jnci.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cyclin D1 in human pituitary tumors: relation to MIB-1 and p27/Kip1 labeling indices

Abstract: Expression of cyclin D1 in pituitary tumors is related to cell proliferation, recurrence, and metastatic potential. Nuclear cyclin D1 expression is a good marker of aggressive behavior in pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In particular, the Ki-67 LI, widely used to determine cellular growth fraction in many types of tumors, is accepted as prognostic indicator in pituitary tumors, although controversial results have emerged from clinical studies and criticisms are also reported in the literature (6,11,12,13,14,15). Other markers have been proposed to assess the aggressiveness of PA, among which pituitary tumor transforming gene, p27, p16, galectin-3, and cyclin D1, but none of them has gained general acceptance as prognostic indicator (9,16,17,18,19,20). Therefore, useful predictors of PA behavior remain to be found for appropriate surveillance and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Ki-67 LI, widely used to determine cellular growth fraction in many types of tumors, is accepted as prognostic indicator in pituitary tumors, although controversial results have emerged from clinical studies and criticisms are also reported in the literature (6,11,12,13,14,15). Other markers have been proposed to assess the aggressiveness of PA, among which pituitary tumor transforming gene, p27, p16, galectin-3, and cyclin D1, but none of them has gained general acceptance as prognostic indicator (9,16,17,18,19,20). Therefore, useful predictors of PA behavior remain to be found for appropriate surveillance and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[17] A recent study suggested new functions of cyclin D1, such as stimulation of cell migration and invasion, enhancement of angiogenesis, regulation of transcription factor activation, induction of chromosomal instability, and control of miRNA expression. [14] However, these findings have not been confirmed by further investigations in PCs.…”
Section: Resultsmentioning
confidence: 99%
“…Kip1 expression than does 45 and in multiple PAs by Bamberger et al 6 and Komatsubara et al; 37 more recently, Hewedi et al 27 compared cyclin D1 expression with p27…”
Section: Kip1mentioning
confidence: 97%
“…8 Overexpression of cyclin D1 is known to be present in a large number of neoplasms, both malignant and nonmalignant, and is one of the most common tumorigenic factors. 27 Despite the widespread nature of cyclin D1 overexpression, however, little published investigation into its role in human PA formation has been definitively shown until recently. In 2011, Hewedi et al 27 showed that the expressions of CCND1 and cyclin D1 were elevated in PAs versus those in the normal pituitary gland.…”
Section: Ccnd1/cyclin D1mentioning
confidence: 99%
See 1 more Smart Citation